Implementation of E-Commerce Website to Increase Online Sales of Case Study of Baby Wise BSD Tangerang - Ahmad, Daelami; Ariessanti, Hani Dewi; Awaliyah, Kholipatul (APTISI Transactions on Management (ATM), 2017)
Today the world of business is growing rapidly so as to stimulate the number of the establishment of companies in various fields. Computers play an important role in every activity in an organization or company. With the computer all the data processing or other important documents can be arranged systematically so that the process of storing and searching data can be more easily and efficiently. Currently there are many companies use the system sales manually, using brochures or print media to find consumers are considered less effective and requires a lot of funds. With the current technological developments, in this study want to try to lift Baby Wise Shop by creating online marketing in the form of website. By using the facilities of computer technology and internet, trying to make sales facilities that can save time then the sales can run well Design sales program created using Dreamweaver CS5, and the database used using Mysql so that the database is stored neatly. The development of this website is expected to be easier for consumers to obtain information about what is offered from Baby Wise Shop. In addition, this online sales website responsive web-based, so that customers can easily buy the latest products, anytime, anywhere want to buy the goods. Keywords​: ​Sales, Information, Customer, Online